PROYECTO DE INVERSIÓN PARA LA CREACIÓN DE UN CENTRO DE DESARROLLO INFANTIL EN LA PARROQUIA ZUMBA DEL CANTÓN CHINCHIPE PROVINCIA DE ZAMORA CHINCHIPE - Jaramillo Vargas, Gaby Andreina (2016)
The thesis entitled "INVESTMENT PROJECT FOR THE CREATION OF A CHILD DEVELOPMENT CENTER IN THE PARISH ZUMBA CANTON CHINCHIPE province of Zamora Chinchipe," was developed along the lines of investigation prepared by the National University of Loja, the same that began with the approach of the objectives; whose overall objective was to demonstrate the relevance of creating a child development center in the parish of Canton Chinchipe Zumba province of Zamora Chinchipe. In the market study market segmentation later to start the analysis of potential demand, real, effective supply and unmet demand which are presented in Tables 13, 14, 15, 20 and 21 was determined respectively; plan market in which the price, place, promotion and advertising also performed detailed. The technical study allowed us to determine the exact location factors where the children's center will be located; project size is also determined by calculating the installed and used which are presented in Tables 23, 24, 25 and 26 respectively capacity. Then the administrative study the legal aspects for the creation of a child development center and regulations to which it will be subject to the achievement and fulfillment of each of the obligations within the center and thus specify develops not infringe with the activities designated for administrative and operational personnel of the company. Finally in the financial analysis indices and financial tools it is applied, such as NPV, IRR, benefit cost, sensitivity analysis, payback period of capital and balance point for achieving these ~ 5 ~ defined that the amount of investment will be $ 143.086,58 funded entirely by the 7 partners; these values are found in Tables 63, 64, 65, 66, 67, 68, 69, 70 and 71 and in graphs 16 and 17 correspondingly. After having prepared the proposed studies it can be concluded that the child development center "Droplets of Love" Cia. Ltda., Has a direct competitor which identified the characteristics of the service provided by the CIBV relative to be provided by the CDI and thus able to offer a quality service to potential customers; for this reason it is recommended to the company that I work according to the guidelines and standards set in the law governing these institutions to thus achieve the ideal service for children under 3 years.